Development of Chalcolithic Phases in Gilund through Ceramic Chronology - Amrita Sarkar; Vasant Shinde (Iranian Journal of Archaeological Studies, 2011)
This paper deals with pottery assemblage from the chalcolithic phase of the site of Gilund in Rajsamand district ofRajasthan. Though pottery from this site has been studied earlier (Shinde et al 2002), however there was no literatureavailable on the ceramic chronology of Gilund with layers ascertained to it. This paper tries to build up a ceramicchronology in the site in order to indentify different phases in the chalcolithic period and ascertain layers to these phases.It further attempts to put forward certain developmental trends and characteristics of chalcolithic pottery for the site ofGilund with probable functional interpretations.